IDENTIFIKASI JENIS TUMBUHAN OBAT DI KAWASAN DESA BATU MEKAR KECAMATAN LINGSAR KABUPATEN LOMBOK BARAT - Husnul Jannah; Safnowandi Safnowandi (Bioscientist : Jurnal Ilmiah Biologi, 2018)
Herbal plant was all kinds of plant while it is cultivated or not yet. It can used as herbal plants. The treatment used plant was long time ago done by our great grandfather since long time ago. It was to legacy with hereditary from generation to generation. To knew how much herbal plant was knew by communities in Batu Mekar Village, Lingsar, West Lombok  and viewed what kind of plant has merit  as medicine , so it needed to do a research activity knew kinds of herbal plants in Batu Mekar. This research was descriptive and explorative research used qualitative and quantitative  approach. With sampling technique was snow ball sampling. The data was collected by  interview with all shaman. The observation to field and documentation . the result of this research showed that the identification kinds of herbal plants in Batu Mekar wasvery kinds. It is found 43 kinds of merit herbal plants its can used for treatment all kinds of illness. The benefit of 43 kinds herbal plants used for treatment illness from small and big illness , and the benefit of all parts from that herbal plants with extraction one plant or mixed with other plant.